Polyimide composite material with polyglutamic acid self-lubricating coating as well as preparation method and application of polyimide composite material

By forming a polyglutamic acid self-lubricating coating on the surface of the polyimide catheter, the problem of internal defects and high surface friction during the high-temperature imidation process is solved, and the stability and friction of the catheter are reduced, which is suitable for high-value medical devices.

CN119524212APending Publication Date: 2025-02-28CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411808478.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Polyimide catheters produce internal defects during high-temperature imidation, which affects their overall performance, and have high surface friction, which may cause damage to human tissue.

Method used

The polyglutamic acid self-lubricating coating is used to connect it to the polyimide matrix through amide bonds to improve the stability and binding force of the coating and reduce the surface friction of the conduit.

Benefits of technology

It improves the stability and wettability of polyimide composite materials, reduces surface friction resistance, improves the overall performance of the catheter, and is suitable for high-value medical devices manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a polyimide composite material with a polyglutamic acid self-lubricating coating as well as a preparation method and application of the polyimide composite material. The polyimide composite material comprises a polyimide matrix and a polyglutamic acid coating formed on the surface of the polyimide matrix. According to the preparation method, a soluble amino-terminated polyimide resin material is firstly prepared through chemical structure design and polymer process optimization, and large-volume non-conjugated groups exist in a polymer molecular structure, so that the interaction between polyimide molecular chains can be destroyed, and the polyimide has excellent solubility in various solvents. Then, the surface of the soluble amino-terminated polyimide resin material is coated with a polyglutamic acid coating, carboxyl in polyglutamic acid can improve the hydrophilicity of polyimide and achieve self-lubrication of polyimide, and carboxyl in polyglutamic acid and amino in polyimide can be subjected to an acid-amine condensation reaction; the binding force between the polyglutamic acid coating and the polyimide resin material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biomedical polymer material preparation, and specifically relates to a polyimide composite material with a polyglutamic acid self-lubricating coating, a preparation method and application thereof, and is particularly suitable for the technical field of high-value medical device manufacturing such as implantation. Background Art

[0002] Polyimide is widely used in many fields due to its excellent comprehensive performance. For example, in the field of medical health, polyimide catheters have great application potential in high-value medical devices such as implants and interventions due to their excellent mechanical properties and biocompatibility. At present, polyimide implantable medical catheter materials have been widely studied and commercial products are available. Patent CN114075385 A discloses a method for preparing medical tubing by mixed coating of polyimide and polyurethane. The tubing prepared by the method can overcome the shortcomings of the hardness of polyimide materials and the large friction of water media, as well as the shortcomings of the poor aging resistance of polyurethane precursor materials. In addition, the polyimide catheters under the trade name of Vasculex® of Essex Furukawa can already be used for medical catheters or biological needle products.

[0003] At present, most polyimide pipes are cured by solid-phase thermal imidization, that is, by coating the pre-prepared polyamic acid slurry into the corresponding shape and then subjecting it to high-temperature imidization. However, small molecules of water will be released during the high-temperature imidization process, causing defects inside the final pipe, affecting its overall performance. In addition, the production and storage and transportation requirements of polyamic acid are relatively high. The solid-phase thermal imidization temperature exceeds 300°C, which also poses great challenges to equipment and energy consumption.

[0004] In addition, implanted catheters need to face a complex in vivo environment. The high friction of the polyimide surface can cause damage to human tissue during the catheter insertion process. Therefore, it is very important to find a method to reduce the surface friction of the polyimide catheter. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a polyimide composite material with a polyglutamic acid self-lubricating coating and a preparation method and application thereof. The polyimide composite material has excellent stability and wettability and low surface friction resistance.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] The present invention provides a polyimide composite material, comprising a polyimide matrix and a polyglutamic acid coating formed on the surface of the polyimide matrix;

[0008] The polyimide matrix and the polyglutamic acid coating are connected via amide bonds.

[0009] Preferably, the polyglutamic acid is γ-polyglutamic acid.

[0010] Preferably, the number average molecular weight of the polyglutamic acid is 10000-100000 Da.

[0011] In a second aspect, the present invention further provides a method for preparing the above-mentioned polyimide composite material, comprising the following steps:

[0012] The slurry containing polyglutamic acid, an activator and a stabilizer is coated on the surface of a soluble amino-terminated polyimide resin main body pipe, and after reaction, a polyimide composite pipe is obtained.

[0013] Preferably, the soluble amino-terminated polyimide resin bulk tube or the soluble amino-terminated polyimide resin bulk film is prepared from a soluble amino-terminated polyimide resin.

[0014] Preferably, the soluble amino-terminated polyimide resin is prepared from diamine monomers and anhydride monomers by a solution thermal imidization method.

[0015] Preferably, the molar ratio of the diamine monomer to the anhydride monomer is 1:(0.95~1).

[0016] Preferably, the solution thermal imidization method is carried out at a temperature of 120-190° C. and a time of 3-9 h.

[0017] Preferably, the activator is selected from 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride.

[0018] Preferably, the stabilizer is selected from N-hydroxysuccinimide.

[0019] Preferably, the solid content of the slurry is 1-7 wt %.

[0020] Preferably, the coating process is repeated 1 to 3 times.

[0021] Preferably, the immersion time is 5 to 60 s.

[0022] Preferably, the reaction temperature is 50-100° C. and the reaction time is 30-120 min.

[0023] Preferably, the reaction is carried out in an inert atmosphere.

[0024] Preferably, the reaction further includes washing and drying steps.

[0025] In a third aspect, the present invention provides a medical catheter, which is formed from the above-mentioned polyimide composite material.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The invention provides a polyimide composite material, comprising a polyimide matrix and a polyglutamic acid coating formed on the surface of the polyimide matrix.

[0028] In the present invention, the preparation method of the above-mentioned polyimide composite material first prepares a soluble amino-terminated polyimide resin material through chemical structure design and polymer process optimization, and the large-volume non-conjugated groups on the surface of the polyimide resin material can destroy the interaction between the polyimide molecular chains, so that it has excellent solubility in a variety of solvents. Then, the present invention coats a polyglutamic acid coating on the surface of the soluble amino-terminated polyimide resin material, wherein the carboxyl group in the polyglutamic acid can improve the hydrophilicity of the polyimide and realize its self-lubrication, and can also react with the amino group in the polyimide to react with acid amine to improve the bonding force between the polyglutamic acid coating and the polyimide resin material, so that the polyglutamic acid coating has excellent stability.

[0029] The preparation method provided by the present invention is simple, convenient, easy to implement, and is conducive to large-scale production or industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a physical picture of the polyimide solid powder in Example 1;

[0031] Figure 2 This is a physical picture of the polyimide tube in Example 1;

[0032] Figure 3 This is a real picture of the polyimide self-lubricating catheter with a γ-polyglutamic acid coating on the surface in Example 1. DETAILED DESCRIPTION

[0033] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Based on the problem in the prior art that the large friction of the polyimide surface may cause damage to human tissue during the introduction of the catheter, the present invention provides a polyimide composite material, including a polyimide matrix and a polyglutamic acid coating formed on the surface of the polyimide matrix.

[0035] In the present invention, the polyimide matrix and the polyglutamic acid coating are connected via an amide bond to improve the bonding force between the matrix and the coating, thereby ensuring the stability of the polyglutamic acid coating.

[0036] In the present invention, the polyglutamic acid is γ-polyglutamic acid, which is prepared by Nanjing Xuankai Biotechnology Co., Ltd. using a microbial fermentation method, and has a number average molecular weight of 10,000 to 100,000 Da, preferably 20,000 to 80,000 Da.

[0037] The present invention also provides a method for preparing the above-mentioned polyimide composite material, comprising the following steps:

[0038] The slurry containing polyglutamic acid, an activator and a stabilizer is coated on the surface of a soluble amino-terminated polyimide resin main body pipe, and after reaction, a polyimide composite pipe is obtained.

[0039] In the present invention, the soluble amino-terminated polyimide resin in the above-mentioned soluble amino-terminated polyimide resin body tube or soluble amino-terminated polyimide resin body film is prepared by a solution thermal imidization method from a diamine monomer and an acid anhydride monomer. At the same time, in order to ensure amino-termining, it is preferred that the amount of the diamine monomer is higher than that of the acid anhydride monomer when feeding. In the present invention, the molar ratio of the diamine monomer to the acid anhydride monomer is preferably 1:(0.95~1), and more preferably 1:(0.95~0.98).

[0040] It should be noted that the present invention specifically selects soluble amino-terminated polyimide resins. Compared with other active group-terminated polyimide resins, the amidation reaction between the amino groups on its surface and the carboxyl groups of polyglutamic acid can better improve the binding force between the two. On the other hand, the reaction conditions are mild, which is conducive to the formation of a polyglutamic acid coating.

[0041] In the present invention, the diamino monomer is selected from any one or more combinations of 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, 4,4'-diaminobenzophenone, 9,9-bis(4-amino-3-tolyl)fluorene, polyetheramine D400, 9,9-bis(4-aminophenyl)fluorene or 2,7-diaminofluorene. The anhydride monomer is selected from any one or more combinations of pyromellitic anhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,4,9,10-tetracarboxylic anhydride, 3,4'-oxydiphthalic anhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride, 4,4'-(4,4'-isopropyldiphenoxy) diphthalic anhydride or 4,4'-(4,4'-isopropyldiphenoxy) diphthalic anhydride.

[0042] In the present invention, the soluble amino-terminated polyimide resin is preferably prepared by a solution thermal imidization method. It can be seen that the polyimide has completed the imidization process in the synthesis stage, so high-temperature imidization is not required in the subsequent stage, which avoids the influence of by-products on the performance of the pipe. The subsequent process only needs to dry the solvent, which is conducive to reducing energy consumption.

[0043] Specifically, the method comprises the following steps:

[0044] After the diamine monomer and the acid anhydride monomer are mixed with a solvent, a water-separating agent and a catalyst, imidization treatment is performed. The mixing is preferably performed in an inert atmosphere under stirring conditions.

[0045] In the present invention, the solvent is selected from any one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N,-methylpyrrolidone, dimethyl sulfoxide, cyclopentane or diphenyl sulfone; the water-separating agent is selected from any one or more of benzene, toluene, xylene or cyclohexane; the catalyst is selected from any one or more of quinoline, isoquinoline, pyridine or 3-methylpyridine.

[0046] In the present invention, the temperature of the imidization treatment is 120-190°C, preferably 130-150°C; the time is 3-9 hours, preferably 4-6 hours. After the imidization treatment, the steps of evaporating the water-separating agent, purifying and drying are generally included, and the obtained product is finally a soluble amino-terminated polyimide solid powder.

[0047] In the present invention, in the above-mentioned imidization system, the monomer concentration is 15-25 wt%, that is, the mass of the diamine monomer and the acid anhydride monomer accounts for 15-25 wt% of the total mass of the diamine monomer, the acid anhydride monomer and the solvent, preferably 18-22 wt%.

[0048] Taking the preparation of soluble amino-terminated polyimide resin bulk pipe as an example, generally three steps are required: core wire laying, slurry coating and solvent drying.

[0049] Wherein, the core wire pay-off rate in the process of pay-off is 0.2~10 m / min, preferably 2~5 m / min.

[0050] The slurry is prepared by compounding a soluble amino-terminated polyimide solid powder with an organic solvent, and the solid content is 10-40 wt%, preferably 20-30 wt%. The organic solvent is any one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N,-methylpyrrolidone or dimethyl sulfoxide. The slurry coating process is preferably repeated 3-5 times.

[0051] The solvent drying process is carried out under vacuum or inert gas protection, at a temperature of 150-200° C., preferably 160-180° C., and is repeated 3-5 times.

[0052] In some embodiments of the present invention, the wall thickness of the soluble amino-terminated polyimide resin body tube is generally 30-60 μm, preferably 40-50 μm.

[0053] In some embodiments of the present invention, taking the pipe as an example, according to the present invention, a slurry containing polyglutamic acid, an activator and a stabilizer is coated on the surface of the soluble amino-terminated polyimide resin body pipe, and after the reaction, a polyimide composite pipe is obtained. In the present invention, the activator is selected from 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, which is used to form a highly activated carboxylic acid derivative with carboxylic acid, making it easier to be attacked by nucleophilic reagents; the stabilizer is selected from N-hydroxysuccinimide, which is used to stabilize the addition intermediate of the first stage carboxylic acid and carbodiimide to prevent the intermediate from rearranging itself to form a corresponding urea byproduct; the solid content of the slurry is 1~7 wt%, preferably 2~5 wt%, and the solid content is the content of polyglutamic acid in the slurry.

[0054] Specifically, the polyglutamic acid coating is formed on the surface of the soluble amino-terminated polyimide resin body pipe, including four steps of slurry coating, pretreatment, water washing and drying, wherein the pretreatment process can realize the reaction between the carboxyl group in the polyglutamic acid and the amino group in the amino-terminated polyimide, and the water washing process can remove the residual catalyst and by-products. The coating process is preferably repeated 1 to 3 times. The pretreatment process is carried out under an inert atmosphere at a temperature of 50 to 100°C, preferably 60 to 80°C; the time is 30 to 120 min, preferably 40 to 100 min. The water temperature of the water washing process is 40 to 60°C, preferably 45 to 50°C, and is repeated 3 to 5 times. The temperature of the drying is 100 to 120°C, preferably 105 to 110°C; the time is 60 to 120 min, preferably 80 to 100 min.

[0055] Taking the preparation of a soluble amino-terminated polyimide resin bulk film as an example, the obtained soluble amino-terminated polyimide solid powder is generally mixed with an organic solvent (the selection of which refers to the above-mentioned relevant content) to obtain a casting solution with a solid content of 10-40 wt%, preferably 20-30 wt%. The casting solution is poured onto a cleaned, dried and leveled glass plate, and after it is leveled, it is dried at a gradient temperature (100°C, 120°C, 140°C, 160°C, 180°C) to obtain a soluble amino-terminated polyimide resin bulk film with a thickness of 30-60 μm.

[0056] In some embodiments of the present invention, taking a film as an example, according to the present invention, a soluble amino-terminated polyimide resin bulk film is immersed in a slurry containing polyglutamic acid, an activator and a stabilizer, and after the reaction, a polyimide composite film is obtained.

[0057] The immersion time is 5 to 60 s, preferably 10 to 50 s, and more preferably 15 to 30 s.

[0058] In the present invention, the reaction is carried out in an inert atmosphere at a temperature of 50-100° C., preferably 60-80° C., and for a time of 30-120 min, preferably 40-100 min.

[0059] After the reaction is completed, the reaction preferably includes water washing and drying, wherein the water temperature of the water washing process is 40-60°C, preferably 45-50°C, and is repeated 3-5 times. The drying temperature is 100-120°C, preferably 105-110°C, and the drying time is 60-120 min, preferably 80-100 min.

[0060] The present invention also provides a medical catheter (such as an implantable catheter), which is formed by the polyimide composite material in the above technical solution.

[0061] The present invention tests the prepared polyimide composite catheter and polyimide composite film and finds that the content of reducing substances in the water extract is ≤1 mL, which is considered to meet the standard; the cell survival rate is ≥70% and is considered to have low cytotoxicity; and the hydrophilicity of the surface of the polyimide composite catheter and the polyimide composite film is significantly improved, and the stability is strong.

[0062] In summary, the above-mentioned polyimide composite material provided by the present invention is a composite of a polyimide matrix and a polyglutamic acid coating, wherein the hydrophilicity of polyglutamic acid gives the polyimide excellent self-lubricating properties, and a large number of carboxyl groups in the molecular structure of polyglutamic acid and the amino groups in the amino-terminated polyimide realize an amidation reaction under the action of an acid-amine condensation activator, thereby realizing an effective combination of the polyglutamic acid coating and the polyimide catheter, improving the interfacial bonding force between the coating and the polyimide matrix, and facilitating the stability of the coating. In addition, the preparation method of the coating of the present invention is scientific and reasonable, and can improve the comprehensive performance of polyimide medical materials (especially polyimide medical catheters) from multiple aspects, making them more suitable for practical application scenarios.

[0063] In order to further illustrate the present invention, the following examples are provided for detailed description. The experimental raw materials used in the following examples of the present invention are all common commercially available products.

[0064] The test methods involved in the following embodiments and comparative examples of the present invention are as follows:

[0065] (1) Test for reducing substance content of water-soluble substances: According to GB / T 14233.1-2022 "Test methods for medical infusion, transfusion and injection equipment Part 1: Chemical analysis methods", the extraction ratio is 0.2 g / mL, the extraction temperature is 37°C, and the extraction time is 72 h. The reducing substance content of the water-soluble substances of the catheter is tested by indirect titration method.

[0066] (2) Cytotoxicity test: The cytotoxicity test of the catheter was carried out in accordance with GB / T 16886.5-2017 "Biological evaluation of medical devices Part 5: In vitro cytotoxicity test".

[0067] (3) Hydrophilicity test: The hydrophilicity test of the composite coating was carried out in accordance with GB / T 30693-2014 "Measurement of the contact angle between plastic film and water";

[0068] (4) Stability test: After the polyimide catheter was immersed in a 50°C water bath for 12 h, a contact angle test was performed.

[0069] Example 1

[0070] (1) Preparation of soluble amino-terminated polyimide resin with 100% fluorene content

[0071] 14.217 g 9,9-bis(4-aminophenyl)fluorene, 6.980 g pyromellitic anhydride, 2.578 g 3,3',4,4'-dibenzophenonetetracarboxylic dianhydride, 130 g N,-methylpyrrolidone, 1.55 g quinoline, 42 g toluene were placed in a three-necked flask equipped with a mechanical stirrer and a water separator. The atmosphere in the flask was replaced with argon and stirred at room temperature for 30 minutes. The oil bath was heated to 160°C and refluxed for 5 hours. During this period, water continued to reflux into the water separator. This is the imidization process. After the reaction was completed, the toluene in the system was evaporated and a strip-like crude product was precipitated in ethanol. After 5 times of purification with ethanol and drying, a yellow-brown polyimide solid powder was obtained, such as Figure 1 shown.

[0072] (2) Preparation of polyimide catheter

[0073] Weigh the obtained polyimide solid powder into a 250 mL HDPE chemical bottle, add DMAC solvent to prepare a composite slurry with a solid content of 20%. Pay out the silver-plated copper wire through the pay-off device, and the core wire enters the ethanol and pure water cleaning tank at a rate of 2 m / min. After cleaning, it is dried. The clean core wire enters the coating area for the first coating, and the coating tank contains the composite slurry. The coated core wire enters the nitrogen atmosphere for solvent drying, and the temperatures are set to 100°C, 150°C and 200°C respectively. After multiple coatings, drying and core extraction, a polyimide catheter with a wall thickness of about 50 μm is obtained, such as Figure 2 shown.

[0074] (3) Composite of polyimide catheter and polyglutamic acid coating

[0075] The obtained polyimide catheter was coated with a coating tank containing a γ-polyglutamic acid / EDC hydrochloride / NHS aqueous solution with a solid content of 5 wt% (the mass ratio of γ-polyglutamic acid to EDC hydrochloride was 10:1, and the mass ratio of EDC hydrochloride to NHS was 2:1). The coated tube was pretreated in a nitrogen atmosphere at a temperature of 100°C for 2 hours. After the pretreatment, a polyimide self-lubricating catheter with a γ-polyglutamic acid coating on the surface was obtained, such as Figure 3 After pretreatment, the catheter was cleaned with deionized water and dried at 100°C for 2 hours. The catheter was used for reducing substance content test and cytotoxicity test of water extract.

[0076] (4) Composite of polyimide film and polyglutamic acid coating

[0077] The obtained polyimide solid powder was weighed into a 20 mL sample bottle, and DMAC solvent was added to fully dissolve it to obtain a casting solution with a solid content of 20%. The casting solution was poured onto a clean, dried and leveled glass plate (10×10 cm). After it was leveled, it was dried at a gradient temperature (100℃, 120℃, 140℃, 160℃, 180℃) to obtain a polyimide film material with a thickness of about 60 μm. The film material was immersed in a γ-polyglutamic acid / EDC hydrochloride / NHS aqueous solution with a solid content of 5wt% (the mass ratio of γ-polyglutamic acid to EDC hydrochloride was 10:1, and the mass ratio of EDC hydrochloride to NHS was 2:1) for 5 seconds and then treated at 100℃ for 2 hours in a nitrogen atmosphere to obtain a polyimide self-lubricating film coated with γ-polyglutamic acid on the surface. The film was washed with deionized water and dried at 100℃ for 2 hours. This film was used for hydrophilicity testing.

[0078] Example 2

[0079] Preparation of 90% soluble polyimide resin, coated composite catheter and coated composite film

[0080] 12.795 g 9,9-bis(4-aminophenyl)fluorene, 6.980 g pyromellitic anhydride, 2.578 g 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 130 g N,-methylpyrrolidone, 1.55 g quinoline, 43 g toluene were placed in a three-necked flask equipped with a mechanical stirrer and a water separator, the atmosphere in the flask was replaced with argon and stirred at room temperature for 30 min. The oil bath was heated to 160°C and refluxed for 1.5 h, during which water continued to reflux into the water separator, which was the imidization process. After this process, the system was cooled to room temperature, 0.817 g 4,4'-diaminodiphenyl ether was added, and the temperature was raised to 160°C again and reacted for 3 h. After the reaction was completed, the toluene in the system was evaporated and a strip-shaped crude product was precipitated in ethanol. It was purified by ethanol 5 times and dried to obtain a yellow-brown polyimide solid powder.

[0081] The preparation of the polyimide catheter, the composite of the polyimide catheter and the polyglutamic acid coating, and the composite of the polyimide film and the polyglutamic acid coating are described in Example 1, except that the polyimide solid powder prepared in Example 2 is used.

[0082] Example 3

[0083] Preparation of 80% soluble polyimide resin, coated composite catheter and coated composite film

[0084] 11.373 g 9,9-bis(4-aminophenyl)fluorene, 6.980 g pyromellitic anhydride, 2.578 g 3,3',4,4'-dibenzophenonetetracarboxylic dianhydride, 122 g N,-methylpyrrolidone, 1.55 g quinoline, 41 g toluene were placed in a three-necked flask equipped with a mechanical stirrer and a water separator, the atmosphere in the flask was replaced with argon and stirred at room temperature for 30 min. The oil bath was heated to 160°C and refluxed for 1.5 h, during which water continued to reflux into the water separator, which was the imidization process. After this process, the system was cooled to room temperature, 1.634 g 4,4'-diaminodiphenyl ether was added, and the temperature was raised to 160°C again and reacted for 3 h. After the reaction was completed, the toluene in the system was evaporated and a strip-shaped crude product was precipitated in ethanol. It was purified by ethanol 5 times and dried to obtain a yellow-brown polyimide solid powder.

[0085] The preparation of the polyimide catheter, the composite of the polyimide catheter and the polyglutamic acid coating, and the composite of the polyimide film and the polyglutamic acid coating are described in Example 1, except that the polyimide solid powder prepared in Example 3 is used.

[0086] Example 4

[0087] Preparation of 70% soluble polyimide resin, coated composite catheter and coated composite film

[0088] 9.952 g 9,9-bis(4-aminophenyl)fluorene, 6.980 g pyromellitic anhydride, 2.578 g 3,3',4,4'-dibenzophenonetetracarboxylic dianhydride, 125 g N,-methylpyrrolidone, 1.55 g quinoline, 42 g toluene were placed in a three-necked flask equipped with a mechanical stirrer and a water separator, the atmosphere in the flask was replaced with argon and stirred at room temperature for 30 min. The oil bath was heated to 160°C and refluxed for 1.5 h, during which water continued to reflux into the water separator, which was the imidization process. After this process, the system was cooled to room temperature, 2.451 g 4,4'-diaminodiphenyl ether was added, and the temperature was raised to 160°C again and reacted for 3 h. After the reaction was completed, the toluene in the system was evaporated and a strip-shaped crude product was precipitated in ethanol. Purified by ethanol 5 times and dried to obtain a yellow-brown polyimide solid powder.

[0089] The preparation of the polyimide catheter, the composite of the polyimide catheter and the polyglutamic acid coating, and the composite of the polyimide film and the polyglutamic acid coating are described in Example 1, except that the polyimide solid powder prepared in Example 4 is used.

[0090] Example 5

[0091] Preparation of 60% soluble polyimide resin, coated composite catheter and coated composite film

[0092] 8.53 g 9,9-bis(4-aminophenyl)fluorene, 6.980 g pyromellitic anhydride, 2.578 g 3,3',4,4'-dibenzophenonetetracarboxylic dianhydride, 118 g N,-methylpyrrolidone, 1.55 g quinoline, 40 g toluene were placed in a three-necked flask equipped with a mechanical stirrer and a water separator, the atmosphere in the flask was replaced with argon and stirred at room temperature for 30 min. The oil bath was heated to 160°C and refluxed for 1.5 h, during which water continued to reflux into the water separator, which was the imidization process. After this process, the system was cooled to room temperature, 3.267 g 4,4'-diaminodiphenyl ether was added, and the temperature was raised to 160°C again and reacted for 3 h. After the reaction was completed, the toluene in the system was evaporated and a strip-shaped crude product was precipitated in ethanol. Purified by ethanol 5 times and dried to obtain a yellow-brown polyimide solid powder.

[0093] The preparation of the polyimide catheter, the composite of the polyimide catheter and the polyglutamic acid coating, and the composite of the polyimide film and the polyglutamic acid coating are described in Example 1, except that the polyimide solid powder prepared in Example 5 is used.

[0094] Example 6

[0095] Preparation of 50% soluble polyimide resin, coated composite catheter and coated composite film

[0096] 7.108 g 9,9-bis(4-aminophenyl)fluorene, 6.980 g pyromellitic anhydride, 2.578 g 3,3',4,4'-dibenzophenonetetracarboxylic dianhydride, 118 g N,-methylpyrrolidone, 1.55 g quinoline, and 35 g toluene were placed in a three-necked flask equipped with a mechanical stirrer and a water separator. The atmosphere in the flask was replaced with argon and stirred at room temperature for 30 minutes. The oil bath was heated to 160°C and refluxed for 1.5 hours. During this period, water continued to reflux into the water separator. This was the imidization process. After this process, the system was cooled to room temperature, 4.085 g 4,4'-diaminodiphenyl ether was added, and the temperature was raised to 160°C again and reacted for 3 hours. After the reaction was completed, the toluene in the system was evaporated and a strip-shaped crude product was precipitated in ethanol. Purified by ethanol 5 times and dried to obtain a yellow-brown polyimide solid powder.

[0097] The preparation of the polyimide catheter, the composite of the polyimide catheter and the polyglutamic acid coating, and the composite of the polyimide film and the polyglutamic acid coating are similar to Example 1, the only difference being that the polyimide solid powder prepared in Example 6 is used.

[0098] Example 7

[0099] 11.373 g 9,9-bis(4-aminophenyl)fluorene, 6.980 g pyromellitic anhydride, 3.554 g hexafluorodianhydride, 140 g N,-methylpyrrolidone, 1.55 g quinoline, and 46 g toluene were placed in a three-necked flask equipped with a mechanical stirrer and a water separator. The atmosphere in the flask was replaced with argon and stirred at room temperature for 30 minutes. The oil bath was heated to 160°C and refluxed for 1.5 hours. During this period, water continued to reflux into the water separator. This was the imidization process. After this process, the system was cooled to room temperature, 3.264 g polyetheramine D-400 was added, and the temperature was raised to 160°C again and reacted for 3 hours. After the reaction was completed, the toluene in the system was evaporated and a strip-shaped crude product was precipitated in ethanol. Purified by ethanol 5 times and dried to obtain a yellow-brown polyimide solid powder.

[0100] The preparation of the polyimide catheter, the composite of the polyimide catheter and the polyglutamic acid coating, and the composite of the polyimide film and the polyglutamic acid coating are similar to Example 1, the only difference being that the polyimide solid powder prepared in Example 7 is used.

[0101] Example 8

[0102] 11.373 g 9,9-bis(4-aminophenyl)fluorene, 6.980 g pyromellitic anhydride, 4.164 g 4,4'-(4,4'-isopropyldiphenyloxy)phthalic anhydride, 141 g N,-methylpyrrolidone, 1.55 g quinoline, 47 g toluene were placed in a three-necked flask equipped with a mechanical stirrer and a water separator, the atmosphere in the flask was replaced with argon gas and stirred at room temperature for 30 minutes. The oil bath was heated to 160°C and refluxed for 1.5 hours, during which water continued to reflux into the water separator, which was the imidization process. After this process, the system was cooled to room temperature, 2.125 g 4,4''-diaminoterphenyl was added, and the temperature was raised to 160°C again and reacted for 3 hours. After the reaction was completed, the toluene in the system was evaporated and a strip-shaped crude product was precipitated in ethanol. It was purified by ethanol 5 times and dried to obtain a yellow-brown polyimide solid powder.

[0103] The preparation of the polyimide catheter, the composite of the polyimide catheter and the polyglutamic acid coating, and the composite of the polyimide film and the polyglutamic acid coating are similar to Example 1, the only difference being that the polyimide solid powder prepared in Example 8 is used.

[0104] Comparative Example 1

[0105] Preparation of polyimide catheters and films with 100% fluorene content (without composite coating treatment)

[0106] The polyimide powder obtained in Example 1 was weighed into a 250 mL HDPE chemical bottle, and DMAC solvent was added to obtain a polyimide slurry with a solid content of 20%. The silver-plated copper wire was released through a wire-releasing device, and the core wire entered the ethanol and pure water cleaning tank at a rate of 2 m / min, and dried after the cleaning was completed. The clean core wire entered the coating area for the first coating, and the coating tank contained the prepared polyimide slurry. The coated core wire entered the oven for solvent drying, and the temperatures were set to 100°C, 150°C, and 200°C, respectively. After multiple coatings, drying and core extraction, a polyimide catheter with a wall thickness of about 50 μm was obtained. The catheter was used for comparative testing of the content of reducing substances in water-soluble substances and comparative testing of cytotoxicity.

[0107] The polyimide powder obtained in Example 1 was weighed into a 20 mL sample bottle, and DMAC solvent was added to fully dissolve it to obtain a casting solution with a solid content of 20%. The casting solution was poured onto a cleaned, dried and leveled glass plate (10×10 cm). After it was leveled, it was dried at a gradient temperature (100°C, 120°C, 140°C, 160°C, 180°C) to obtain a polyimide film material with a thickness of about 60 μm. This film was used for hydrophilicity comparison test.

[0108] Comparative Example 2

[0109] Preparation of polyimide catheter and film with 90% fluorene content (without composite coating treatment)

[0110] The polyimide powder obtained in Example 2 was weighed into a 250 mL HDPE chemical bottle, and DMAC solvent was added to prepare a polyimide slurry with a solid content of 20%. The remaining steps of catheter preparation and performance testing were the same as those of Comparative Example 1.

[0111] The polyimide powder obtained in Example 2 was weighed into a 20 mL sample bottle, and DMAC solvent was added to fully dissolve it to prepare a casting solution with a solid content of 20%. The remaining steps of film preparation and performance test were the same as those of Comparative Example 1.

[0112] Comparative Example 3

[0113] Preparation of polyimide catheter and film with 80% fluorene content (without composite coating treatment)

[0114] The polyimide powder obtained in Example 3 was weighed into a 250 mL HDPE chemical bottle, and DMAC solvent was added to prepare a polyimide slurry with a solid content of 20%. The remaining steps of catheter preparation and performance testing were the same as those of Comparative Example 1.

[0115] The polyimide powder obtained in Example 3 was weighed into a 20 mL sample bottle, and DMAC solvent was added to fully dissolve it to prepare a casting solution with a solid content of 20%. The remaining steps of film preparation and performance test were the same as those of Comparative Example 1.

[0116] Comparative Example 4

[0117] Preparation of polyimide catheter and film with 70% fluorene content (without composite coating treatment)

[0118] The polyimide powder obtained in Example 4 was weighed into a 250 mL HDPE chemical bottle, and DMAC solvent was added to prepare a polyimide slurry with a solid content of 20%. The remaining steps of catheter preparation and performance testing were the same as those of Comparative Example 1.

[0119] The polyimide powder obtained in Example 4 was weighed into a 20 mL sample bottle, and DMAC solvent was added to fully dissolve it to prepare a casting solution with a solid content of 20%. The remaining steps of film preparation and performance test were the same as those of Comparative Example 1.

[0120] Comparative Example 5

[0121] Preparation of polyimide catheter and film with 60% fluorene content (without composite coating treatment)

[0122] The polyimide powder obtained in Example 5 was weighed into a 250 mL HDPE chemical bottle, and DMAC solvent was added to prepare a polyimide slurry with a solid content of 20%. The remaining steps of catheter preparation and performance testing were the same as those of Comparative Example 1.

[0123] The polyimide powder obtained in Example 5 was weighed into a 20 mL sample bottle, and DMAC solvent was added to fully dissolve it to prepare a casting solution with a solid content of 20%. The remaining steps of film preparation and performance test were the same as those of Comparative Example 1.

[0124] Comparative Example 6

[0125] Preparation of polyimide catheter and film with 50% fluorene content (without composite coating treatment)

[0126] The polyimide powder obtained in Example 6 was weighed into a 250 mL HDPE chemical bottle, and DMAC solvent was added to prepare a polyimide slurry with a solid content of 20%. The remaining steps of catheter preparation and performance testing were the same as those of Comparative Example 1.

[0127] The polyimide powder obtained in Example 6 was weighed into a 20 mL sample bottle, and DMAC solvent was added to fully dissolve it to prepare a casting solution with a solid content of 20%. The remaining steps of film preparation and performance test were the same as those of Comparative Example 1.

[0128] Comparative Example 7

[0129] Preparation of polyimide self-lubricating film with 100% fluorene content (no activator or stabilizer is added to the composite coating)

[0130] The polyimide powder obtained in Example 1 was weighed into a 20 mL sample bottle, and DMAC solvent was added to fully dissolve it to obtain a casting solution with a solid content of 20%. The casting solution was poured onto a clean, dried and leveled glass plate (10×10 cm), and after it was leveled, it was dried by gradient heating (100°C, 120°C, 140°C, 160°C, 180°C) to obtain a polyimide film material with a thickness of about 60 μm. The film material was immersed in a γ-polyglutamic acid aqueous solution with a solid content of 5wt% for 5 seconds and then treated at 100°C for 2 hours under a nitrogen atmosphere to obtain a polyimide self-lubricating film with a γ-polyglutamic acid coating on the surface.

[0131] Performance Testing

[0132] The test results of reducing substance content of water extracts of the samples obtained in the above examples and comparative examples are shown in Table 1:

[0133] Table 1

[0134] Group Reducing substance content (mL) Example 1 0.44 Example 2 0.66 Example 3 0.53 Example 4 0.65 Example 5 0.69 Example 6 0.70 Comparative Example 1 0.67 Comparative Example 2 0.52 Comparative Example 3 0.66 Comparative Example 4 0.71 Comparative Example 5 0.63 Comparative Example 6 0.67

[0135] The present invention is tested by indirect titration method, the amount of reducing substances is expressed by the amount of potassium permanganate solution consumed, and the reducing substance content of the water extract is ≤1 mL, which is considered to meet the standard.

[0136] The cytotoxicity test results of the samples obtained in the above examples and comparative examples are shown in Table 2:

[0137] Table 2

[0138] Group Cell survival rate (%) Negative 100 Positive 0.6023 Example 1 73.2562 Example 2 74.6845 Example 3 75.9251 Example 4 76.2320 Example 5 76.4658 Example 6 73.4866 Comparative Example 1 75.5649 Comparative Example 2 75.1523 Comparative Example 3 73.6680 Comparative Example 4 73.2652 Comparative Example 5 76.3230 Comparative Example 6 75.4660

[0139] It can be seen from the data in Table 2 that the cell survival rates of the prepared tubes are all greater than 70%, and have low cytotoxicity (cell survival rates ≥ 70% are considered to be low cytotoxicity).

[0140] The hydrophilicity test results of the samples obtained in the above examples and comparative examples are shown in Table 3:

[0141] Table 3

[0142] Group Water contact angle (°) Example 1 26.2 Example 2 22.5 Example 3 25.5 Example 4 25.3 Example 5 24.0 Example 6 20.7 Comparative Example 1 75.3 Comparative Example 2 77.2 Comparative Example 3 80.3 Comparative Example 4 75.6 Comparative Example 5 77.3 Comparative Example 6 72.7

[0143] From the comparison between the examples and the comparative examples in Table 3, it can be seen that after the composite coating treatment, the hydrophilicity of the surface of the polyimide catheter is significantly improved.

[0144] The hydrophilicity test results (coating stability) of the samples obtained in the above Examples 1-6 and Comparative Example 7 after being immersed in a 50° C. water bath for 12 hours are shown in Table 4:

[0145] Table 4

[0146] Group Water contact angle (°) Example 1 25.2 Example 2 22.9 Example 3 27.5 Example 4 25.8 Example 5 25.0 Example 6 22.6 Comparative Example 7 67.3

[0147] It can be seen from the data in Table 4 that the surface hydrophilicity of the polyimide film treated with the coating without adding activator and stabilizer decreases significantly after water washing, indicating that the coating without adding activator and stabilizer cannot form a stable bonding force with the polyimide film substrate, and the coating is severely damaged after water washing.

[0148] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A polyimide composite material, characterized in that: It comprises a polyimide matrix and a polyglutamic acid coating formed on the surface of the polyimide matrix; The polyimide matrix and the polyglutamic acid coating are connected via amide bonds.

2. The polyimide composite material according to claim 1, characterized in that: The polyglutamic acid is γ-polyglutamic acid; The number average molecular weight of the polyglutamic acid is 10000-100000 Da.

3. A method for preparing a polyimide composite material according to claim 1 or 2, characterized in that: The following steps are involved: The slurry containing polyglutamic acid, an activator and a stabilizer is coated on the surface of a soluble amino-terminated polyimide resin main body pipe, and after reaction, a polyimide composite pipe is obtained.

4. The preparation method according to claim 3, characterized in that: The soluble amino-terminated polyimide resin body tube or the soluble amino-terminated polyimide resin body film is prepared from a soluble amino-terminated polyimide resin; The soluble amino-terminated polyimide resin is prepared from diamine monomers and anhydride monomers by a solution thermal imidization method; The molar ratio of the diamine monomer to the anhydride monomer is 1:(0.95-1).

5. The preparation method according to claim 4, characterized in that: The temperature of the solution thermal imidization method is 120-190° C. and the time is 3-9 h.

6. The preparation method according to any one of claims 3 to 5, characterized in that The activator is selected from 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride; The stabilizer is selected from N-hydroxysuccinimide; The solid content of the slurry is 1-7 wt %.

7. The preparation method according to any one of claims 3 to 6, characterized in that The coating process is repeated 1 to 3 times; The immersion time is 5 to 60 s.

8. The preparation method according to any one of claims 3 to 7, characterized in that The reaction temperature is 50~100 ℃, and the time is 30~120 min; The reaction is carried out in an inert atmosphere.

9. The preparation method according to any one of claims 3 to 8, characterized in that The reaction is followed by washing and drying steps.

10. A medical catheter, characterized in that: The invention is formed by the polyimide composite material according to claim 1 or 2 or the polyimide composite material prepared by the preparation method according to any one of claims 3 to 9.

Citation Information

Patent Citations

  • Medical tube and preparation method thereof

    CN114075385A